The role of Sharia financing product in improving company management at PT Mandiri Utama Finance - Mattarima, Mattarima; Wijana, Moh. Arga; Suaeb, Muh. Irwan; Rusli, Muhammad; Ista, Akram; Kadir, Syahruddin (Universitas Islam Indonesia, 2026)
IntroductionSharia financing (Rahn) has become an alternative to consumer financing in Indonesia. The implementation of Rahn financing at multifinance companies in South Sulawesi requires further study to understand its role in corporate management and strengthen the companies’ competitiveness.ObjectivesThis study examines the role of Sharia financing product (Rahn) for PT Mandiri Utama Finance South Sulawesi, focusing on the company’s implementation and operational management.MethodThis study employs a qualitative approach using a case study design at PT Mandiri Utama Finance South Sulawesi. Research data were collected through semi-structured interviews, field observations, and analysis of company documents. The analysis technique used a thematic analysis approach to identify patterns, experiences, and findings related to the implementation of Rahn financing at PT Mandiri Utama Finance South Sulawesi.ResultsThe Rahn product implemented by MUF South Sulawesi is in accordance with the DSN-MUI Fatwa. The Rahn contract application process requires collateral in the form of gold and identification, and the estimated value of the collateral is based on market prices. The Rahn product has enhanced the company’s operational management by driving business growth and increasing corporate profits through the acquisition of new customers, market share expansion, and organizational sustainability. This signifies the expansion of financial inclusion, particularly for segments of society requiring quick and easy access to financing without complex procedures, while also strengthening the company’s competitive position.ImplicationsThis study emphasizes the importance of product innovation and Sharia compliance in Sharia-based financing, such as in Rahn. However, challenges remain, including limited understanding among some customers regarding the Rahn financing mechanism, intense competition with conventional financing institutions, and limited human resources in the sector. Therefore, this study recommends that PT MUF strengthen its customer education strategy, enhance its human resource training, and develop digital service innovations to improve the company’s efficiency and competitiveness.Originality/NoveltyThis study provides insights into how Islamic financial products can serve as a new strategy for multifinance companies to balance innovation and tradition to strengthen management capabilities and drive sustainable growth. It offers new empirical contributions regarding how Rahn product are applied within the context of Islamic multifinance companies.